2022
DOI: 10.3389/fpsyg.2022.913406
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Chronic Obstructive Pulmonary Disease: Perspectives on the Use of Hypnosis

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is a highly prevalent and debilitating respiratory condition, characterized by chronic airflow limitation, breathlessness, and other persistent respiratory symptoms. Critically, patients suffering from COPD often find themselves trapped in a vicious comorbidity cycle: while breathlessness and increased respiratory rate are known inducers of anxiety, the latter have been shown in turn to exacerbate breathlessness and chest discomfort. Hypnosis holds great potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
0
0
2
Order By: Relevance
“…The present study demonstrated that patients with respiratory diseases, who reported daily health symptoms, are more likely to experience mental health problems such as depression, anxiety, and stress. These findings are consistent with previous studies [15], suggesting that respiratory health symptoms may directly contribute to the development of psychological problems [16]. In addition, during high-pollution periods, people with respiratory comorbidities, particularly air pollution, are vulnerable to the severity of health symptoms [17].…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrated that patients with respiratory diseases, who reported daily health symptoms, are more likely to experience mental health problems such as depression, anxiety, and stress. These findings are consistent with previous studies [15], suggesting that respiratory health symptoms may directly contribute to the development of psychological problems [16]. In addition, during high-pollution periods, people with respiratory comorbidities, particularly air pollution, are vulnerable to the severity of health symptoms [17].…”
Section: Discussionsupporting
confidence: 91%
“…Çalışmaya katılan hastaların yaş ortalamasının 63,87±10,77 (38-88) yıl olduğu, %58'inin erkek, %71'inin evli, eğitim durumunun %74'ünde ilköğretim ve %57'sinin emekli olduğu belirlendi. KOAH tanı süresi ortalaması 9,35±9,01 (1-46) yıl, son bir yıl içinde hastalığın alevlenme sayısı 2,00±2,58 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), hastane yatışı sayısı 1,47±0,50 (1-2) olarak bulundu. Hastaların yarısı sigara kullanmayı bıraktığını, %21'i devam ettiğini ifade etti.…”
Section: Bulgularunclassified
“…[6][7][8][9] KOAH ile anksiyete, depresyon ve intihar eğilimi başta olmak üzere psikolojik komorbiditeler arasında çift yönlü ilişki olduğu tutarlı olarak bildirildi. [10][11][12] Mevcut veriler, bireyin KOAH semptomlarının yönetiminin ve tedaviye uyumunun sağlanmasının yanı sıra psikososyal olarak değerlendirilmesinin ve müdahale edilmesinin de önemini göstermektedir. Hastaların psikososyal uyumunu desteklemek, psikolojik müdahalelerin temel amacıdır ve tedavi ekibinin önemli rollerinden biridir.…”
Section: Introductionunclassified